CORRESPONDENCE ANALYSIS OF FRUIT AND VEGETABLE WASTE AMONG CONSUMERS IN VOJVODINA - Ubiparip Samek, Dragana (Food and Feed Research, 2022)
Fresh fruit and vegetables contribute to almost 50% of food wasted by households in the EU. To understand the main reasons for wasteful behaviour among the consumers in Vojvodina (Serbia) cross-sectional data were collected through a self-administrated online survey of 711 correspondents. The questions presented in the study focused on the method of preserving the fruits and vegetables in domestic conditions before their consumption. Self-estimation of wasteful behaviour in the household and socio-demographic factors, including the respondents’ self-estimated health status, were analysed using the correspondence analysis. The results showed that the first two dimensions explained for 95.06% of the total per cent of inertia (statistically significant at p<0.001 level) indicating the strong relationship among variables. According to the survey, the fruit and vegetables are most likely used fresh (54.43% and 48.95%, respectively), whereas the use of fruits and vegetables after storage in a refrigerator (17.16% and 29.96%, respectively) or in a deep freezer (2.81% or 5.20%, respectively) is significantly lower. Most of the survey correspondents claimed that they regularly discard the fruits and vegetables to waste (53.02% and 39.66%, respectively). The results pointed out that the storage and the amounts of discarded waste are affected by gender, income, and health conditions of the respondents’. Also, the study emphasized the growing need for educating and better planning of fresh fruit and vegetable management to reduce waste production.